2015
DOI: 10.1155/2015/642652
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Cytomegalovirus in Different Histopathological Types of Glioma in Iraqi Patients

Abstract: Human Cytomegalovirus (HCMV) is an endemic herpes virus that reemerges in cancer patients enhancing oncogenic potential. HCMV infection is associated with certain types of cancer morbidity such as glioblastomas. HCMV, like all other herpes viruses, has the ability to remain latent within the body of the host and can contribute in chronic inflammation. To determine the role of HCMV in glioma pathogenesis, paraffin-embedded blocks from glioma patients (n = 50) and from benign meningioma patients (n = 30) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Most of this debate stems from the fact that different research groups, often using different assays, have generated evidence to support or refute the presence of HCMV in GBM tumors. There is a large amount of research supporting both sides of this issue (Amirian, Bondy, Mo, Bainbridge, & Scheurer, 2014; Baryawno et al, 2011; Baumgarten et al, 2014; Cosset et al, 2014; Fornara et al, 2016; Hashida et al, 2015; Holdhoff et al, 2015; Joseph, McDermott, Baryshnikova, Cobbs, & Ulasov, 2017; Khoury et al, 2013; Lehrer, Green, Rosenzweig, & Rendo, 2015; Libard et al, 2014; McFaline-Figueroa & Wen, 2017; Prins, Cloughesy, & Liau, 2008; Rahbar et al, 2012; Sardi et al, 2015; Schelhorn et al, 2013; Shamran et al, 2015; Solomon, Ramkissoon, Milner, & Folkerth, 2014; Stangherlin et al, 2016; Strong et al, 2016; Wolmer-Solberg et al, 2013) that we summarize in Fig. 1B–D.…”
Section: Introductionmentioning
confidence: 91%
“…Most of this debate stems from the fact that different research groups, often using different assays, have generated evidence to support or refute the presence of HCMV in GBM tumors. There is a large amount of research supporting both sides of this issue (Amirian, Bondy, Mo, Bainbridge, & Scheurer, 2014; Baryawno et al, 2011; Baumgarten et al, 2014; Cosset et al, 2014; Fornara et al, 2016; Hashida et al, 2015; Holdhoff et al, 2015; Joseph, McDermott, Baryshnikova, Cobbs, & Ulasov, 2017; Khoury et al, 2013; Lehrer, Green, Rosenzweig, & Rendo, 2015; Libard et al, 2014; McFaline-Figueroa & Wen, 2017; Prins, Cloughesy, & Liau, 2008; Rahbar et al, 2012; Sardi et al, 2015; Schelhorn et al, 2013; Shamran et al, 2015; Solomon, Ramkissoon, Milner, & Folkerth, 2014; Stangherlin et al, 2016; Strong et al, 2016; Wolmer-Solberg et al, 2013) that we summarize in Fig. 1B–D.…”
Section: Introductionmentioning
confidence: 91%
“…Primary CMV infection has lifelong persistence, mostly an asymptomatic infection in a human host, and results in the development of a lifelong carrier status with periodic reactivation and shedding of the virus from mucosal sites [ 11 , 16 ]. Previous studies demonstrated that CMV is associated with various diseases, including cardiovascular disease (CVD) [ 14 , 15 , 17 19 ], those affecting cognitive functioning [ 20 , 21 ], tumor [ 22 ], and type 2 diabetes mellitus [ 3 , 23 ], and even mortality [ 4 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cosset et al, [53] [60] On the other hand, several recent studies have reported no association between HCMV and GBM. One study utilized several approaches including a prospective and retrospective analysis to detect the presence of HCMV in tissue, plasma, and serum of high-grade glioma (HGG) patients.…”
Section: Authors Number Of Samples Analyzed Detection Methods Analytementioning
confidence: 97%